Updated checklist of Cuban marine macroalgae - Suárez, Ana M.; Martínez-Daranas, Beatriz; Alfonso Sánchez, Yusimí; Moreira-González, Ángel R.; Jover Capote, Abdiel (Instituto de Ecología, A.C., 2023)
Background and Aims: Since the publication of the book on Cuban marine macroalgae in 2015, new records have been found and taxonomic changes have been published. Therefore, the objective of this publication is to present a fifth updated systematic review, that includes Ochrophyta (Class Phaeophyceae), Rhodophyta and Chlorophyta. Methods: These results were recorded from information available in scientific papers, bachelor, master and doctoral theses, as well as scientific-technical reports from recognized specialists, considering those not included in the last review or that were published after 2015. The taxa were systematically ordered, the names and synonymy were reviewed according to Algaebase and the most recent scientific literature. Species were arranged alphabetically within each family. The distribution of each taxon was resumed for nine Ecological Districts (zones) of the Cuban shelf.Key results: An updated floristic list with 569 species, one subspecies, 25 varieties, and 21 forms is presented. Thirty-seven species are added to the previous review of which seven are new records for Cuba: Hydrolithon boergesenii, Neogoniolithon mamillare, N. propinquum, N. rhizophorae, Lithothamnion crispatum, Liagoropsis schrammii, and Peyssonnelia rubra. The distribution of these taxa in the nine zones of the Cuban shelf is provided.Conclusions: The zones showing more species have had a greater sampling effort or were predominantly rocky reef bottoms. However, macroalgae have not been inventoried in detail in the intertidal zone, bays, and coastal lagoons. Zones with fewer species coincide in having a narrower shelf where rocky substrates dominate, although macroalgae have not been inventoried in the intertidal zone, bays, and coastal lagoons.